2010
DOI: 10.1186/1471-2334-10-349
|View full text |Cite
|
Sign up to set email alerts
|

Detection of multiple strains of Mycobacterium tuberculosis using MIRU-VNTR in patients with pulmonary tuberculosis in Kampala, Uganda

Abstract: BackgroundMany studies using DNA fingerprinting to differentiate Mycobacterium tuberculosis (MTB) strains reveal single strains in cultures, suggesting that most disease is caused by infection with a single strain. However, recent studies using molecular epidemiological tools that amplify multiple targets have demonstrated simultaneous infection with multiple strains of MTB. We aimed to determine the prevalence of MTB multiple strain infections in Kampala, and the impact of these infections on clinical present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
37
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 19 publications
9
37
2
Order By: Relevance
“…Nationality was considered for the first time as a factor influencing the occurrence of mixed infections; however, it was not significantly associated with mixed infections in our study, an observation that is similar to that with many other previously reported factors (Table 3) (7,8,43). From our data, there was a trend Non-Beijing (2, 100) …”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Nationality was considered for the first time as a factor influencing the occurrence of mixed infections; however, it was not significantly associated with mixed infections in our study, an observation that is similar to that with many other previously reported factors (Table 3) (7,8,43). From our data, there was a trend Non-Beijing (2, 100) …”
Section: Discussionsupporting
confidence: 76%
“…Older people, who normally have a poorer immune response, and those with immunosuppressive conditions, such as HIV infection, were considered to be associated with mixed infections to a higher extent (8,44). The sensitivity of the Xpert MTB/ RIF assay for RIF resistance detection was reduced in the cases of mixed infections and in HIV-infected patients who may suffer mixed infections (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of studies on clonal complexity in M. tuberculosis infection has increased in recent years (8,10,18). However, some of these studies examine anecdotal cases (2) and others analyze this phenomenon only in specific M. tuberculosis lineages (35) or specific phenotypes (34).…”
Section: Discussionmentioning
confidence: 99%
“…However, some of these studies examine anecdotal cases (2) and others analyze this phenomenon only in specific M. tuberculosis lineages (35) or specific phenotypes (34). Those which follow population-based designs to determine the proportion of clonally complex TB cases are performed mainly in epidemiological contexts with a markedly high incidence of TB (8,10,29,30,35) and/or where the possibility of overexposure is more likely (28).…”
Section: Discussionmentioning
confidence: 99%